2023
DOI: 10.1177/21582440231206367
|View full text |Cite
|
Sign up to set email alerts
|

Is the Effect of Organizational Ambidexterity and Technological Innovation Capability on Firm Performance Mediated by Competitive Advantage? An Empirical Research on Turkish Manufacturing and Service Industries

Derya Çelik,
Ülkü Uzunçarşılı

Abstract: The strategic management literature reveals that organizational ambidexterity (OA) and technological innovation capabilities (TIC) have separate effects on competitive advantage (CA) and firm performance (FP). However, these two capabilities have not been investigated simultaneously and in comparison with the sector. The main aim of this study is to reveal the mediating role of CA in the effect of OA and technological innovation capabilities on FP. Using the research model based on quantitative data, the prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 129 publications
1
1
0
Order By: Relevance
“…In line with Hensellek [151] and Venugopal et al [152], the results revealed a positive relationship between DL and DGT. This aligns with prior research by Marsh [153] and Çelik and Uzunçarşılı [154], emphasizing the pivotal role of DL in organizational change. However, the study extends this understanding by demonstrating that higher DL levels among managers lead to more effective DGT initiatives.…”
Section: Discussionsupporting
confidence: 89%
“…In line with Hensellek [151] and Venugopal et al [152], the results revealed a positive relationship between DL and DGT. This aligns with prior research by Marsh [153] and Çelik and Uzunçarşılı [154], emphasizing the pivotal role of DL in organizational change. However, the study extends this understanding by demonstrating that higher DL levels among managers lead to more effective DGT initiatives.…”
Section: Discussionsupporting
confidence: 89%
“…Companies can continuously progress and augment financial performance through technological innovations such as new product development [41,42]. In the recent study by Çelik and Uzunçarşılı (2023) [43], it was found that technological innovation capability has a positive impact on firm performance, and competitive advantage partially mediates this relationship. Additionally, technical innovation capability is considered relevant to long-term strategic success.…”
Section: Technological Capabilitymentioning
confidence: 99%